Risks and risk mitigation in global software development: An update. Issue 11 (23rd September 2021) - Barros‐Justo, José L.; Benitti, Fabiane B. V.; Molleri, Jefferson S.
Abstract: Context: Interest in global software development (GSD) has led to the publication of numerous studies. Over time, these studies should be updated to verify if their findings and conclusions remain valid. Objective: To update a tertiary study, published in 2014, focused on investigating risks and risk mitigation advice in the context of GSD. Method: We conducted a systematic literature study based on forward snowballing, out of which we identified and selected 25 unique studies. Results: We extracted: (a) 118 risks (75 of which already identified in the original work), and (b) 167 mitigation advice (44 of which were identified in the original work). Out of 43 new risks identified, just 10 are specific to GSD settings; the others are risks of the software process described in the context of GSD. The evidence supporting these risks and mitigation were extracted from 619 and 389 primary sources, respectively. Given the amount of evidence found, we have reported only those with higher empirical support. The raw data is available online as complementary material. Conclusions: Interest in GSD, its potential risks, and mitigation strategies, remains high. This update has allowed increasing the level of empirical support provided by the findings of the original work.